2008
DOI: 10.1007/s11096-008-9236-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes from the use of Medication Report when elderly patients are discharged from hospital

Abstract: The Medication Report seems to be an effective tool to decrease adverse clinical consequences when elderly patients are discharged from hospital care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 22 publications
(22 reference statements)
0
45
0
1
Order By: Relevance
“…However in the latter study, we did not evaluate the quality of the discharge summary, and the errors were measured at discharge based on the discharge summary and not when patients returned to primary care as was the case in this study. The latter study also showed a reduction in clinical consequences based on medication errors [20]. In our previous descriptive study, there were an average of 2.4 medication errors per patient at admission to the hospital, and only 15% of the patients had no errors at all [18].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However in the latter study, we did not evaluate the quality of the discharge summary, and the errors were measured at discharge based on the discharge summary and not when patients returned to primary care as was the case in this study. The latter study also showed a reduction in clinical consequences based on medication errors [20]. In our previous descriptive study, there were an average of 2.4 medication errors per patient at admission to the hospital, and only 15% of the patients had no errors at all [18].…”
Section: Discussionmentioning
confidence: 64%
“…The medication report has also been shown to significantly reduce morbidity and thus the need for medical care due to medication errors in the elderly [20]. However, the study did not evaluate the content and correctness of the medication report, so there is room for further improvement in the process, which is the basis for this study.…”
Section: Introductionmentioning
confidence: 99%
“…Medication errors are, however, also frequent at the interface between levels of care [31][32][33]. In order to minimise this problem, we have also developed and evaluated separate methods for use at admission to [34] and discharge from [35][36][37] hospital. These studies contribute to the evidence of the usefulness of the entire in-hospital patient care process model, the LIMM model, which comprises a model of care from admission, through the hospital stay to discharge and transferral of the patient back to primary or community care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the individual LIMM-tools have been shown to reduce unidentified DRPs during the patients" hospital stay (20) and reduce the need for health care contacts caused by medication errors (21). These findings describe outcomes for the patient, but we were also interested in how the model is appreciated by the health care personnel and how it affects the daily work regarding DRPs.…”
Section: The Process Of Identifying Solving and Preventing Drug Relamentioning
confidence: 99%